Is 'Difficult Heritage' Still 'Difficult'?: Why Public Acknowledgment of Past Perpetration May No Longer Be So Unsettling to Collective Identities. Issue 1 (21st June 2016) - Macdonald, Sharon
Abstract: This article discusses 'difficult heritage' as the phenomenon of nations or other collectives publicly signaling and commemorating past atrocities that they committed and for which they are ashamed. Through a focus on public commemoration and heritage of World War II in Europe, it shows that there has long been reluctance to acknowledge such potentially identity‐disrupting pasts. This, however, is changing, with Germany at the forefront of a turn towards more frequent public addressing of unsettling pasts in museums and heritage sites. The article argues that this turn entailed some fundamental conceptual shifts, including changes in understandings of the agency of the past, of how best to tackle trauma and of the purpose of public remembering. The consequence of this, it maintains, is that addressing difficult heritage is no longer necessarily identity‐disrupting in the way that it was formerly. Indeed, on the contrary, rather than being 'difficult' in this sense, it can be ¬– and increasingly is – regarded as having positive identity effects.